In Silico Evaluation of New Fluoroquinolones as Possible Inhibitors of Bacterial Gyrases in Resistant Gram-Negative Pathogens - Manuel Alejandro Coba-Males; Javier Santamaría-Aguirre; Christian D. Alcívar-León (Chemistry Proceedings, 2021)
The work seeks to identify molecules with inhibitory activity against the DNA gyrase of Gram-negative microorganisms resistant to fluoroquinolones. Previously designed compounds were used to study antimicrobial potential in silico. Molecular docking was performed with nine new ciprofloxacin analog molecules, optimized through the PM6/ZDO theory level, in GyrA wild type (WT) and mutant type (MT) of C. jejuni, E. coli (6RKU PDB ID), N. gonorrhoeae, P. aeruginosa, S. enteritidis, and S. typhi. The molecule with the highest affinity for GyrA was selected based on its binding free energy and inhibition constant. In addition, a retrospective docking was carried out, to guarantee the correct affinity of the ligand to the receptor at the defined binding site. The results show a molecule with greater affinity for GyrA in five microorganisms, showing a binding free energy of less than −7.0 kcal/mol, suggesting a good antibacterial activity in silico.